O ensino de ciências por meio das plataformas digitais e as dificuldades enfrentadas pelos discentes em uma universidade pública em meio à pandemia da covid-19 - Silva, Carmen Malafaia (Brasil, 2022)
This research will address the issue of teaching science through digital platforms and the difficulties faced by students at a public university in the midst of the covid-19 pandemic. With regard to education, due to social isolation as a protective measure to prevent the spread of the SARS-COV-2 virus, recommended by the World Health Organization (WHO), this had to be rethought, to assist elementary school students. and higher. To continue classes, Higher Education Institutions opted for Remote Teaching, using Information and Communication Technologies (ICTs) as teaching tools, but at first only a few implemented remote activities. In this perspective, the main difficulties that some Universities are facing are internet access and lack of electronic equipment, such as smartphones, tablets and notebooks. In this context are included the universities and institutes of the interior of the state of Amazonas. Therefore, this research aimed to investigate the teaching and learning practices of students in the subjects in the teaching of the Science course: Biology and Chemistry during remote teaching. For that, a bibliographic survey, descriptive, documentary, qualitative research was carried out. The target audience of this research are academics from the Institute of Nature and Culture/INC, from the Science course: Biology and Chemistry. In the documental analysis, the steps that the University and the Institute decided on related to the buildings, teaching, research, extension and work of technicians and others that form the group of workers of the same are demonstrated; in the face of the Covid-19 pandemic, adopting necessary measures of protection and responsibility with health, and means to continue classes, such as remote/hybrid teaching. Through the data obtained through the questionnaire, three main points were analyzed: adaptation to remote teaching, changes resulting from this type of teaching in the students' daily lives and quality in teaching and learning. Therefore, this research in the face of the experience shared by the students, we understand that the universities were not prepared, even with the EAD modality, but it is not the same thing. Therefore, this research allowed us to know the reality of higher education students at a public university located in the Alto Solimões region. As a future teacher, this study allows me to rethink the identity that I build in graduation before the pandemic and to outline new possibilities for methodologies that can be well developed for better teaching and learning, mainly using ICTs, and carrying out research in order to keep up with the pace of innovations in education.